[Rezension von: Healing fractures in contemporary theology] - Daniel, Michael E. (The Australasian Catholic record, 2023)
Review(s) of: Healing fractures in contemporary theology, ed. Peter John McGregor and Tracey Rowland, (Eugene, OR: Cascade Books, 2022), pp. 286, paperback, $40.10.